Necrotic spotting on barley leaves associated with Erysiphe graminis infection and other factors - Sutherland, Karene Gardner (The University of Edinburgh, 1989)
Although brown lesions on barley leaves are usually attributable to a readily defined parasitic or non -parasitic factor, the causes of certain forms of necrotic spotting are sometimes more difficult to explain. A classification is given of the types of symptoms that may present diagnostic problems and the symptom types are associated with particular cultivars. In some cases necrotic responses to powdery mildew infection were related to cultivar, but, for other cultivars, relatively severe symptoms of brown spotting occurred independently of mildew. The results of experimental work indicated that where nutrient deficiencies gave rise to browning, the symptoms produced were generally characteristic of the mineral element involved rather than the cultivar, but that cultivar- specific symptoms were associated with herbicide injury or high temperature stress. Saprophytic organisms or deposits of pollen on leaves could not be implicated in the browning process. Observations from in vitro culture work with barley plantlets grown aseptically from embryos suggested that certain cultivars might be predisposed to accumulate high phenolic concentrations in response to stress, and this might be indicative of vulnerability to cultivar- related browning in the fields. Histological examinations showed differences between brown lesions due to mildew infection and those due to other, cultivar- related, factors. From a review of studies on brown spotting symptoms in barley leaves, it is suggested that genetic factors which render cultivars prone to visible necrotic responses to stress stimuli represent a potential source of yield reduction.